2023
DOI: 10.3389/fpubh.2023.1153256
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ozone exposure-induced fracture

Abstract: IntroductionOzone (O3) is known to induce oxidative stress that influences various cells and tissues, which may further lead to diminished bone mineral density. Nevertheless, few studies have investigated the association between O3 exposure and fractures. Considering the similar growing trends of O3 concentrations and fracture morbidity in recent years, in the present study, we aimed to examine whether O3 exposure is associated with the fracture morbidity.MethodsUsing a retrospective cohort study design, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis indicated that exposures to PM10, PM2.5, and NOx played negative roles in decreased BMD and increased the risk of osteoporotic fracture [ 38 ]. In addition, a retrospective cohort study has observed a positive association between ozone exposure and the risk of bone fracture development, potentially through ozone-induced oxidative stress injury that causes loss of bone mass [ 39 ]. This evidence suggests a positive association between long-term air pollutant exposure and bone damage, whereas, owing to the limitations of observational studies, they cannot rule out causality between air pollutants and bone health, thus previous observed findings may not always be generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicated that exposures to PM10, PM2.5, and NOx played negative roles in decreased BMD and increased the risk of osteoporotic fracture [ 38 ]. In addition, a retrospective cohort study has observed a positive association between ozone exposure and the risk of bone fracture development, potentially through ozone-induced oxidative stress injury that causes loss of bone mass [ 39 ]. This evidence suggests a positive association between long-term air pollutant exposure and bone damage, whereas, owing to the limitations of observational studies, they cannot rule out causality between air pollutants and bone health, thus previous observed findings may not always be generalizable.…”
Section: Discussionmentioning
confidence: 99%